Applications of price sensitivity measurement to analyze perceptions of gasoline prices in Thailand - Ariyasena, Hiruni Menusha; Surachet Pravinvongvuth; Kunnawee Kanitpong (Pathum Thani : Asian Institute of Technology, 2018)
Gasoline is very important ware in a country. Gasoline has different prices in different coun- try. And perceptions about gasoline prices are different from person to person. This study mainly focuses on perception of gasoline prices in Thailand. It focuses on socio demographic characteristics. There were six characteristics as age, personal income, vehicle ownership, education level, occupation and how long using public transportation. It focuses on over- all price of gasoline also. For this 10,000 travelers were taken. Data were collected from a questionnaire. This study will provide you the optimal price of gasoline found by using Price Sensitivity Method. These data were collected in February 2018. This research will provide which socio demographic characteristics have relationship with gasoline prices and how they connect with overall gasoline price. And this study shows how the people react to higher tax collection and how they give cope/handle way to gasoline prices.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Civil and Infrastructure Engineering
Capstone Project (B.Sc.)-Asian Institute of Technology, 2018
Keywords: Gasoline -- Prices -- Thailand